Essential MATLAB for engineers and scientists. - Hahn, Brian D.; Hahn, Brian D.; Valentine, Daniel T., 1946- (Amsterdam : Academic Press, 2013)
The fifth edition of Essential MATLAB for Engineers and Scientists provides a concise, balanced overview of MATLAB's functionality that facilitates independent learning, with coverage of both the fundamentals and applications. The essentials of MATLAB are illustrated throughout, featuring complete coverage of the software's windows and menus. Program design and algorithm development are presented clearly and intuitively, along with many examples from a wide range of familiar scientific and engineering areas.This is an ideal book for a first course on MATLAB or for an engineering problem-solving course using MATLAB, as well as a self-learning tutorial for professionals and students expected to learn and apply MATLAB. Updated with the features of MATLAB R2012b. Expanded discussion of writing functions and scripts. Revised and expanded Part II: Applications. Expanded section on GUIs. More exercises and examples throughout
Editions 1 & 2 published as: Essential MATLAB for scientists and engineers; editions 3-5 as: Essential MATLAB for engineers and scientists.
Includes index.
Tặng
Keywords: MATLAB; Engineering mathematics -- Data processing